Thermohaline Temporal Variability of the SE Mediterranean Coastal Waters (Israel) – Long-Term Trends, Seasonality, and Connectivity - Ozer, Tal; Gertman, Isaac; Gildor, Hezi; Herut, Barak (Frontiers in Marine Science, 2022)
The high variability of coastal waters together with the growing need for assessing the state of the marine coastal ecosystem, require continuous monitoring at exceptional resolution and quality, especially during the Anthropocene changing seas. We perform a comprehensive analysis of a decadal (March 2011 to June 2021) thermohaline variability of the East Levantine Basin (LB) coastal waters (continuous measurements), its predominating temporal trends and their linkage with atmospheric forcing and advection. We identify statistically significant long-term warming and salinification trends with yearly rates of 0.048°C and 0.006, respectively. Through the use of the X11-ARIMA method temperature and salinity inter-annual trends are examined and associated with previously published open ocean dynamics as well as model reanalysis. We study the linkage between Northern and Southern coastal locations, and identify the along shore northward current as a primary cause of positive temperature anomalies arriving from the south. The coastal salinity long-term trend demonstrates a connection to local precipitation. A less coherent seasonal sequence is found with a bimodal behavior, where, salinity values drop in August on several summers. This drop is attributed to the intensification of the along shore current in the period of June-July, potentially advecting more Atlantic Water. The observations presented here emphasize the relatively strong coupling between coastal water and the open ocean, the influence of the general surface circulation of the LB on the coastal zone and the faster response time and higher sensitivity of the coastal environment to atmospheric forcing.